Circadian clustering of spontaneous epileptic seizures emerges after pilocarpine‐induced status epilepticus. (24th May 2017) - Pitsch, Julika; Becker, Albert J.; Schoch, Susanne; Müller, Johannes Alexander; de Curtis, Marco; Gnatkovsky, Vadym
Summary: Objective: Seizures in mesial temporal lobe epilepsy (MTLE) associated with hippocampal sclerosis are thought to develop with various latency intervals after an initial transient brain insult. To study seizure dynamics after an initial transient precipitating insult in a systematic fashion, we utilized continuous video–electroencephalography (EEG) monitoring after the induction of status epilepticus (SE) in a mouse MTLE model. Methods: Continuous 24/7 video/telemetric hippocampal EEG recordings in the systemic pilocarpine MTLE mouse model. Results: After SE, we observed emerging seizures interfering with the circadian EEG rhythms. The physiologic circadian EEG pattern of mice was transiently suppressed for 2.9 (mean) ± (SEM) 0.5 days after SE. This period was accompanied predominately by nonconvulsive seizure activity, followed by convulsive seizures at later stages. After the circadian rhythm was restored, spontaneous generalized seizures occurred mainly in a clustered manner in a narrow time window between 4 and 7 p.m. (light cycle 7 a.m./7 p.m.). Moreover, we demonstrate that depth‐electrode implantation surgery transiently disturbs the physiologic EEG circadian cycle; variation of the time point of SE induction after electrode insertion surgery revealed a substantial impact on the epilepsy phenotype, which was more severe when SE occurred after postsurgical reappearance of EEG circadian cycling. Significance: These data have several experimental and pathophysiologic implications. The impact of depth‐electrode surgery on the phenotype has to be tightly controlled. In mice monitored after pilocarpine‐induced SE, the "epileptogenesis" period is characterized by the dynamics of epileptiform activity toward behavioral recurrent seizure patterns. The striking clustering of spontaneous seizures at the transition from sleep to activity stages of mice has to be taken into account for future studies on the model. Improving our understanding of the molecular mechanisms that determine the circadian dynamics of seizure threshold remains an intriguing task for the future.